2014
DOI: 10.5194/isprsarchives-xl-1-211-2014
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of ice-dam collapse by time-lapse photos at the Perito Moreno glacier, Argentina

Abstract: Commission I, WG I/2 KEY WORDS: time-lapse, information extraction, ice-dam change, Perito Moreno ABSTRACT:This research provides a feasibility study on the implementation and performance assessment of time-lapse processing of a monoscopic image sequence, acquired by a calibrated camera in the Perito Moreno Glacier in Argentina. The glacier is located at 50° 28' 23''S, 73° 02' 10''W at the Parque Nacional Los Glaciares, South Patagonia Icefield, Santa Cruz and has experienced minor fluctuations and unusual beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Time-lapse terrestrial photography is commonly used in polar and alpine regions to study the dynamics of glaciers or to follow the detachment of icebergs (Lenzano et al 2014, Medrzycka et al 2016). Underwater time-lapse studies in coastal polar regions are uncommon due to the intrinsic limitations of scientific SCUBA diving at sub-zero temperatures, the logistical challenges linked to the deployment of large-size and heavy time-lapse arrays and the risk of loss of the photo/video systems that may be misplaced or destroyed by iceberg scouring.…”
Section: Introductionmentioning
confidence: 99%
“…Time-lapse terrestrial photography is commonly used in polar and alpine regions to study the dynamics of glaciers or to follow the detachment of icebergs (Lenzano et al 2014, Medrzycka et al 2016). Underwater time-lapse studies in coastal polar regions are uncommon due to the intrinsic limitations of scientific SCUBA diving at sub-zero temperatures, the logistical challenges linked to the deployment of large-size and heavy time-lapse arrays and the risk of loss of the photo/video systems that may be misplaced or destroyed by iceberg scouring.…”
Section: Introductionmentioning
confidence: 99%
“…The SPI is drained by several outlet glaciers, which calve on sea water and proglacial lakes, creating strong rivers that are significant for the development of human activities in arid environments (De Angelis, 2014; Smith and Evans, 2007). Pre-existing studies have shown that the SPI is changing dramatically (Aniya and Skvarca, 2012; Lenzano et al, 2014, 2018; Lo Vecchio et al, 2018; Minowa et al, 2017; Moragues et al, 2018; Mouginot and Rignot, 2015; Rivera et al, 2012; Sakakibara and Sugiyama, 2014; Skvarca et al, 2002, 2004; Stuefer et al, 2007; Sugiyama et al, 2011, 2016; Warren et al, 1995; among others). The SPI has a strong east–west precipitation gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, photogrammetric image sequence analysis techniques were also successfully applied to serve as a virtual gauge within the framework of an early warning system for GLOF events (Mulsow et. al., 2013) or to investigate ice-dam collapses (Lenzano et. al., 2014).…”
Section: Introductionmentioning
confidence: 99%